Site-specific alloying through binder jet 3D printing - Chiang, Po-Ju (2023)
Controlling the properties of materials site-specifically enables the design and production of multifunctional parts that satisfy multiple constraints at once. In this work, we demonstrate the capability of tuning the mechanical properties of steel site-specifically by varying the local alloy composition through binder jet 3D printing. We deposit a modified binder containing carbon nanoparticles to produce samples with carbon-rich regions that display > 90 % higher hardness compared to the rest of the part. We discuss this feature in terms of carbon diffusion—the limiting factor in site-specific alloying in our case-study material—which we mitigate by employing a 2-stage sintering strategy of our design. Our results showcase new opportunities to design and produce multi-functional metal alloys by controlling the distribution of their alloying elements with an unprecedented level of detail.